Effect of socioeconomic status on functional and motor recovery after stroke: a European multicentre study. Issue 6 (8th December 2006) - Putman, Koen; De Wit, Liesbet; Schoonacker, Miranda; Baert, Ilse; Beyens, Hilde; Brinkmann, Nadine; Dejaeger, Eddy; De Meyer, Anne-Marie; De Weerdt, Willy; Feys, Hilde; Jenni, Walter; Kaske, Christiane; et al.
Abstract : Background: Previous studies have shown an inverse gradient in socioeconomic status for disability after stroke. However, no distinction has been made between the period in the stroke rehabilitation unit (SRU) and the period after discharge. The purpose of this study was to examine the impact of education and equivalent income on motor and functional recovery for both periods. Methods: 419 consecutive patients were recruited from six SRUs across Europe. The Barthel Index (BI) and Rivermead Motor Assessment (RMA) were measured on admission, at discharge and 6 months after stroke. Ordinal logistic regression models were used, adjusting for case mix. Cumulative odds ratios (OR) were calculated to measure differences in recovery between educational levels and income groups with adjustments for case mix. Results: Patients with a low educational level were less likely to improve on the BI (OR 0.53; 95% CI 0.32 to 0.87) and the RMA arm during inpatient stay (OR 0.54; 95% CI 0.31 to 0.94). For this period, no differences in recovery were found between income groups. After discharge, patients with a low equivalent income were less likely to improve on all three sections of the RMA: gross function (OR 0.20; 95% CI 0.06 to 0.66), leg and trunk (OR 0.22; 95% CI 0.09 to 0.55) and arm (OR 0.30; 95% CI 0.10 to 0.87). No differences were found for education. Conclusions: During inpatient rehabilitation, educational level was a determinant of recovery, while after discharge, equivalent income played an important role. This study suggests that it is important to develop a better understanding of how socioeconomic factors affect the recovery of stroke patients.